2017
DOI: 10.4049/jimmunol.1601532
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Fumarate Selectively Reduces Memory T Cells and Shifts the Balance between Th1/Th17 and Th2 in Multiple Sclerosis Patients

Abstract: Dimethyl fumarate (DMF; trade name Tecfidera™) is an oral formulation of the fumaric acid ester that is FDA approved for treatment of relapsing-remitting multiple sclerosis (RRMS). To better understand the therapeutic effects of Tecfidera and its rare side-effect of progressive multifocal leukoencephalopathy (PML), we conducted cross-sectional and longitudinal studies by immunophenotyping cells from peripheral blood (particularly T lymphocytes) derived from untreated, 4-6 month and 18-26 month Tecfidera-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
137
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(175 citation statements)
references
References 58 publications
23
137
2
Order By: Relevance
“…S1). The mother of the patient had several immune-related disorders including multiple sclerosis (MS), arthritis, and recurrent infections, and was receiving 17 different medications at the time of blood sampling, including dimethyl fumarate (DMF), which has been shown to selectively decrease memory T cell populations in MS patients (39). For these reasons and the lack of access, we did not further investigate the mother.…”
Section: Resultsmentioning
confidence: 99%
“…S1). The mother of the patient had several immune-related disorders including multiple sclerosis (MS), arthritis, and recurrent infections, and was receiving 17 different medications at the time of blood sampling, including dimethyl fumarate (DMF), which has been shown to selectively decrease memory T cell populations in MS patients (39). For these reasons and the lack of access, we did not further investigate the mother.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we identified several genetic factors and compounds that interfere with IFNc-induced MHCII expression (Fig 6). CXCR3 is a receptor for CXCL9 and CXCL10 [83]. Dimethyl fumarate (DMF) has recently been FDA approved for the treatment of relapsing-remitting MS, but its exact mechanism of action is still under debate [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings indicated that DMF reduced the number of CD4 + , CD8 + , Th1, and Th17 cells, whereas the CD4 + /CD8 + ratio and the Th2 subset were increased in the blood of these patients. Interestingly, the inhibitory effects of DMF/MMF on T cell activation were confined mainly to memory T cells (Wu et al, 2017). These immunomodulatory activities of DMF or MMF are important for the protection of oligodendrocytes against ROS-induced cytotoxicity (Scannevin et al, 2012).…”
Section: A Electrophilic Nuclear Factor (Erythroid-derived 2)-like 2mentioning
confidence: 99%